Flora Botton (coord.), Historia mínima de China, México, El Colegio de México, 2010, 356 pp. - Anne Staples (Estudios de Asia y África, 2011)
Flora Botton (coord.), Historia mínima de China, México, El Colegio de México, 2010, 356 pp.